2023
DOI: 10.1007/s10531-022-02534-2
|View full text |Cite
|
Sign up to set email alerts
|

Standardized butterfly surveys: comparing transect counts and area-time counts in insect monitoring

Abstract: The observed insect decline, which threatens agricultural productivity and ecosystem stability, calls for comprehensive international insect monitoring. Monitoring implementation demands standardisation and the integration of new and innovative methods. Therefore, we compared two quantitative butterfly survey methods – the commonly applied transect counts (or ‘Pollard walks’) and more extensive area-time counts. We evaluated the influence of the two methods on the estimation of biodiversity variables such as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
0
0
0
Order By: Relevance
“…However, in recent years, an increasing number of studies have used a 50-m long transect or divided a long transect into sections of a 50-m transect for survey and analysis, depending on the conditions of the study site, and have obtained effective results (i.e., Modified Pollard transects) [39][40][41]. In particular, Barkmann et al [42] demonstrated the effectiveness of a 50-m long transect for both population monitoring at the regional scale and for local site comparison regarding diversity and overall habitat quality. However, it is necessary for the survey of butterflies to set up the 50 m transects apart from each other.…”
Section: Study Areamentioning
confidence: 99%
“…However, in recent years, an increasing number of studies have used a 50-m long transect or divided a long transect into sections of a 50-m transect for survey and analysis, depending on the conditions of the study site, and have obtained effective results (i.e., Modified Pollard transects) [39][40][41]. In particular, Barkmann et al [42] demonstrated the effectiveness of a 50-m long transect for both population monitoring at the regional scale and for local site comparison regarding diversity and overall habitat quality. However, it is necessary for the survey of butterflies to set up the 50 m transects apart from each other.…”
Section: Study Areamentioning
confidence: 99%
“…and 6:00 pm. (Westphal et al 2008;Barkmann et al 2023). Rounds were chosen randomly over the full margin.…”
Section: Pollinator and Floristic Surveysmentioning
confidence: 99%